Critical Analysis of the Implementation of the Right to Be Forgotten in Addressing Digital Stigma and Personal Data Protection in Indonesia - Alfin Suherman; Abdullah Sulaiman (Ridwan Institute, 2026)
The development of information and communication technology has led to an increased distribution of personal data in the digital space, which has the potential to give rise to various legal issues, one of which is the emergence of digital stigma against individuals who have been involved in criminal justice processes. Information about criminal cases spread through digital media often remains available and easily accessible to the public even after the individual has been declared innocent by the court. This study critically analyzes the implementation of the Right to Be Forgotten (RTBF) in addressing digital stigma and personal data protection within Indonesia's criminal justice system. Using normative juridical methods with a conceptual approach and descriptive qualitative analysis. The person's social life, career prospects, and reputation may all suffer as a result of this illness. Thus, in the digital age, the idea of the Right to Be Forgotten (RTBF) is an essential legal tool for safeguarding personal information and individual privacy rights. The study's conclusions show that while the Indonesian legal system has adopted the Right to Be Forgotten idea, there are still a number of obstacles in the way of its actualization, including unclear data deletion mechanisms, conflicts between individual privacy protection and judicial system transparency, and technical obstacles in deleting digital information. Therefore, To guarantee that the Right to Be Forgotten can successfully safeguard people's rights to privacy and reputation in the digital era, more stringent laws and clear implementation procedures are needed.